Analisis Kinerja Strategis Perusahaan Menggunakan Metode IFAS Dan EFAS Pada CV Nuansa Sejahtera Indonesia: Strategic Performance Analysis of Companies Using the IFAS and EFAS Methods at CV Nuansa Sejahtera Indonesia - Mila Natalia; Usran Masahere (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the strategic performance of CV Nuansa Sejahtera Indonesia using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach, operationalized through the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) methods. The evaluation was conducted to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that influence the sustainability and development of the company. Data were collected through observation and in-depth interviews with the company leader as the primary informant who understands the company’s operational and business environment. The IFAS analysis resulted in a score of 2.85, indicating that the company possesses relatively dominant internal strengths despite several weaknesses, particularly in digital promotion effectiveness and resource management. Meanwhile, the EFAS analysis produced a score of 2.70, showing that the company is reasonably capable of responding to opportunities arising from marketing technology advancements and increasing market demand, while still facing threats from intense competition and changing consumer preferences. Overall, based on the SWOT analysis, CV Nuansa Sejahtera Indonesia is in a relatively stable strategic position but requires improvement strategies, especially in marketing and human resource development, to enhance competitiveness and long-term sustainability.